DEVELOPMENT OF COMPUTER VISION BASED SMART SYSTEM FOR BROILER CHICKENS HEAT STRESS RECOGNITION - Iqbal Anggoro Agung, Muhammad
In 2022, approximately 80% of the Indonesian population’s demand for protein sources comes from poultry meat, which requires farmers to optimize poultry farming practices. Broiler chickens, a commonly raised poultry breed in Indonesia, requires optimal farming processes. To ensure this, the Feed Conversion Ratio (FCR) is used as one of the parameters to determine the effectiveness of the farming process. Livestock welfare, crucial for growth rates and FCR, can be monitored through computer vision technology. This research aims to develop an intelligent behavior recognition system for broiler chickens to assist operators in monitoring chicken welfare in commercial coops using a computer vision-based Precision Livestock Farming (PLF) method.